دور التلوينات المناعية النسيجية الهرمونيةER) ,PR Her2/neu,) و Ki-67)) في التصنيف الجزيئي لسرطان الثدي وعلاقتها بالإنذار - أحمد, عيسى; داود, علي; حسن, بثينة (Latakia University Journal -Medical Sciences Series, 2019)
Background: Breast cancer is very frequent and has social and psychological implications from the beginning of diagnosis to palliative treatment. Malignant breast tumors are heterogeneous group of diseases that show wide variation in biological behavior, treatment and prognosis relating therapeutic predictive approach to tumors. Methods: Molecular classification of breast malignancies were classified into five groups based on histological immunohistochemistry (IHC) ER, PR, Her2 / neu, Ki-67. 100 samples from Tishreen University Hospital patients with cancer of unilateral and invasive ductal or lobular carcinomas were selected to study the molecular classification method (IHC) during the period 2017-2018, we analyzed the relationship of molecular classification with different warning factors age, tumor size, patterns and histological status and lymph nodes status Axillary, using cross-sectional analytical and statistical study using SPSS. Results: 77 ductal carcinomas, Luminal A (24.7%), Luminal B (24.7%), HER2-enriched (16.9%), Triple- negative (26%) and Normal like (7.8%). we found 23 lobular carcinomas, Luminal A (17.4%), Luminal B (47.8%), HER2-enriched (4.3%), Triple- negative (8.7%) and Normal like (21.7%). We observe the order of molecular patterns starting from the worst warning: Luminal B Triple-Negative or basal like, luminal A, HER2-enriched, normal like. Conclusion: Molecular classification of breast cancers is useful in developing treatment strategies and identifying prognosis الخلفية: يعد سرطان الثدي كثير التواتر وله انعكاسات اجتماعية ونفسية من بداية التشخيص وحتى العلاج الملطف. ورم الثدي الخبيث مجموعة أمراض غير متجانسة تظهر تبايناً واسعا ًبالسلوك البيولوجي والعلاج والإنذار. الطريقة: من أجل المقاربة العلاجية والتنبؤية لهذه الأورام، قد تم تصنيف جزيئي لخباثات الثدي إلى تحت خمس مجموعات اعتماداً على التلوينات المناعية النسيجية (IHC) ER,PR , Her2/neu ,Ki-67 . تم اختيار 100 عينة من مرضى مستشفى تشرين الجامعي لديهم سرطانه قنوية أو فصيصة غازية وحيدة الجانب لدراسة التصنيف الجزيئي بطريقة (IHC) خلال الفترة 2017-2018، وقمنا بإيضاح علاقة التصنيف الجزيئي مع عوامل الإنذار المختلفة: العمر، حجم الورم، الأنماط والدرجة النسيجية وحالة العقد اللمفية الإبطية، باستعمال دراسة احصائية تحليلية – مقطعية عرضية باستخدام برنامج (SPSS). النتائج: كانت النتائج 77 سرطانه قنوية، Luminal A (24.7%), Luminal B (24.7%), HER2-enriched (16.9%), Triple- negative (26% ) و Normal like (7.8%). وجد 23 سرطانة فصيصية، Luminal A (17.4%), Luminal B (47.8%), HER2-enriched (4.3%), Triple- negative (7.8%) و Normal like (21.7%). نلاحظ ترتيب الأنماط الجزيئية بدءاً من الأسوأ إنذاراً: Luminal B Triple-Negative or basal like, luminal A, HER2-enriched, normal like, . الخلاصة: أن التصنيف الجزيئي لسرطانات الثدي مفيد في وضع استراتيجيات العلاج وتحديد الإنذار.